The Role of Career Plateau as a Mediating Variable between Work Ethics and Organizational Commitment of Administrative Staff at One of Regional Hospitals in Jakarta - Roebianto, Adiyo; Fassa, Aulia Anisyah; Hediana, Khansa; Radyani, Muthi’ah Humaira; Sugiarto, Annisa Aulia; Wicaksono, Dimas Aryo (TAZKIYA Journal of Psychology, 2025)
Organizational commitment is an important factor in determining whether someone will be actively involved in carrying out their work duties and also helps determine the achievement of the organization. However, not all employees of the organization have high organizational commitment, including administrative staff at the Regional General Hospital (RSUD). This study aims to see the organizational commitment influenced by the career plateau and work ethic of administrative staff at one of the RSUDs in the Jakarta area. This study uses a quantitative approach with 62 participants (n = 62) and data analysis techniques using mediator regression analysis. Data collection was carried out using a questionnaire accessed via the google form link. This study was conducted at one of the RSUDs in the Jakarta area. The results of the analysis show that work ethic has a more dominant direct effect on the organizational commitment of administrative staff at the RSUD (β = .271), rather than its indirect effect through career plateau (β = .089). This shows that work ethic has a more consistent impact on the loyalty of administrative staff at the RSUD.